Sobre a "mulatização" da literatura : o caso do escritor Hugo Loetscher - Dewulf, Jeroen (2001)
Does it still make sense in the 21st century to divide literature according to the culture or even the country to which it "belongs"? This question is raised in relation to Hugo Loetscher a writer who has traditionally been classified as a "German-speaking Swiss writer". In this article, I present an analysis of his work in a way that is as global and as hybrid as the world in which we live, introducing him as a "mulattised writer".